2021
DOI: 10.1002/anie.202114681
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons as a New Class of Promising Cathode Materials for Aluminum‐Ion Batteries

Abstract: As an emerging post-lithium battery technology, aluminum ion batteries (AIBs) have the advantages of large Al reserves and high safety, and have great potential to be applied to power grid energy storage. But current graphite cathode materials are limited in charge storage capacity due to the formation of stage-4 graphite-intercalated compounds (GICs) in the fully charged state. Herein, we propose a new type of cathode materials for AIBs, namely polycyclic aromatic hydrocarbons (PAHs), which resemble graphite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…Thus far, there have been a small number of studies on organic positive electrodes with aluminum (Al) metal, with a focus on quinone-based molecules, though the nature of the electroactive ions is still poorly understood. Kim et al performed the first investigation of discrete organic molecules for Al batteries using an organic phenanthrene quinone (PQ) macrocycle where they proposed monovalent AlCl 2 + as the electroactive ion via a combination of time-of-flight secondary ion mass spectrometry (TOF-SIMS) and energy-dispersive X-ray (EDX) spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there have been a small number of studies on organic positive electrodes with aluminum (Al) metal, with a focus on quinone-based molecules, though the nature of the electroactive ions is still poorly understood. Kim et al performed the first investigation of discrete organic molecules for Al batteries using an organic phenanthrene quinone (PQ) macrocycle where they proposed monovalent AlCl 2 + as the electroactive ion via a combination of time-of-flight secondary ion mass spectrometry (TOF-SIMS) and energy-dispersive X-ray (EDX) spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) display unique molecular geometries, electronic, optical and magnetic properties, making these compounds suitable for applications in organic electronics, photonics, spintronics, and energy storage. [1][2][3][4][5][6] In addition, PAHs are an important subject in environmental and astrochemistry. [7][8][9] Müllen and his coauthors have successfully implemented a bottom up approach for the synthesis of large PAHs.…”
Section: Introductionmentioning
confidence: 99%
“…This way, the heteroatom doping significantly changes the geometry, electronic and solubility properties with respect to the parent PAH molecule. Although, N-doped positively charged PAHs have been synthesized more than thirty years ago, [19] the interest for such systems started growing after Müllen and his coauthors [20] have shown that the arrangement of 9-phenyl-benzo [1,2]quinolizino [3,4,5,6-fed]phenanthridinylium in superstructures can be modulated by choosing proper anions. The synthesis, self-assembly and electronic properties of ionic N-doped PAHs have attracted much attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] In addition, PASs can function as platforms for electrocatalysis, 11 redox-active materials, 12 and organic electrode materials. 13,14 The development of improved organic electronic devices, such as light emitting diodes (OLEDs), 15 field effect transistors (OFETs), 5,16,17 solar cells (OSCs), 2,8 sensors, 18 and semiconductors 10,16,17,19 hinges on the design of new functional PASs. With the decreasing cost of computational resources and the concurrent advent of machine-learning (ML) and deep-learning (DL) techniques, data-driven design of molecules and materials for various uses has become an increasingly promising approach.…”
Section: Introductionmentioning
confidence: 99%